Violenza, politica e civilité tra filosofia e politica - Dodaro, Rita; Cacciatore, Fortunato Maria; Perrelli, Raffaele (Università della Calabria, 2023)
My thesis wants to analyze the different and complex semantic and pragmatic stratifications which build the concept of violence, starting from the polysemy and the ambivalence of the German term Gewalt. For this reason, my fundamental point of reference is Walter Benjamin’s thought: the investigation starts from the “Critique of Violence” (Gewalt). In this analysis, other basic terms of Benjamin's philosophical-political lexicon are relevant: eg. Herrschaft and Macht. These words, together with Gewalt, highlight the concept of state, traditionally referred to that concentration of power able to subdue individuals to itself, in particular those individuals who gave up their rights to receive peace and security in exchange.
Dottorato di ricerca internazionale di Studi umanistici: Testi, saperi, pratiche: dall’antichità classica alla contemporaneità, Ciclo XXXV, a.a. 2022-2023
Keywords: Violenza; Politica; Civilté; Benjamin Balibar